Caracterización fitoquímica y evaluación de actividad Antimicrobiana y Antioxidante de Dendrophthora elliptica (Gardner) Krug & Urb. (Santalaceae). - Coronel Dávalos, Johana Narcisa (2014)
It was determined the chemical composition, antimicrobial activity and antioxidant activity in the samples extracts that were obtained by maceration of the dried leaves of Dendrophthora elliptica with solvents of increasing polarity was determined through techniques commonly used as phytochemical screening, disk diffusion and DPPH respectively. It was found in the extracts: oils and fats, triterpenes, steroids, catechins, saponins, reducing sugars, alkaloids, lactones and cumarins, phenols and tannins, flavonoids, amino acids and bitter substances. Antibacterial activity was found for S. aureus, P. aeruginosa, and E. coli with an CMI of 100 mg/ml in aqueous extract and ethereal extract; 50 mg/ml in ethanolic extract; 25 mg/ml in aqueous extract, and 40 mg/ml in ethereal extract, respectively.